Governance and Public Expenditure: The Case of Sub-Saharan African (SSA) Countries - Madina Dankumo, Ali; Lado, Sulaiman; Auta, Yusuf; Shadrach, Bulus (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Public expenditure is considered a means of supplying public goods and services and accelerating economic growth through government consumption. Government spending on infrastructures like health, agriculture, education, energy, rural development, transport and communication enhances growth and development.This paper examines the relationship between governance (corruption and political instability) and public expenditure with other control variables, using Pooled Mean Group (PMG) to tackle the problem of heterogeneity from 1996 to 2017 of 34 SSA countries. The results revealed a long-run relationship between governance, trade, income, debt service, population growth and government consumption expenditure as a % of GDP in the SSA region. Specifically, both corruption and political instability reduce government consumption expenditure in countries with low governance, whereas in countries with very low governance, it's only corruption that increases government consumption, which means corruption contributes more to governance than political instability. Trade, income, debt service and population are also significant determinants of government consumption expenditure. This outcome implies that governance is a determinant of government consumption in the SSA region. We recommend that Anti-corruption agencies should ensure enforcement of their laws and compliance with the code of ethics for public officers – declaring assets they may have in private investments- to ensure they do not turn richer above their earnings through corrupt activities.